New insight into Feldstein and Horioka Paradox: Analyzing the mediating roles of globalization, urbanization, and foreign direct investment. Issue 2 (30th September 2020) - Akadiri, Seyi S.; Apinran, Martins O.; Usman, Nurudeen
Abstract : Different dimensions abound to examine the famous Feldstein–Horioka Puzzle. However, after intense discussions of the subject matter for more than three decades, researchers are yet to reach consensus on the validity or otherwise of savings–investment relationship. In this paper, we revisited the Feldstein–Horioka saving‐investment puzzle, and augment their investment equation with factors that drive capital mobility, such as globalization, foreign direct investment, and urbanization using more recent annual frequency time series data over the periods 1981–2018 in the case of Nigeria. We employed unit root test with structural breaks/regime shifts inherent in time series data and Autoregressive Distributed Lag Bounds Testing for co‐integration of empirical estimates. Results show existence of a long‐run equilibrium relationship among variables. Domestic savings, real income, and foreign direct investment reveal positive impact, while globalization and urbanization exhibit negative impact on domestic investment both in the short and long run. We find strong capital mobility among savings–investment relationship, thus render potential policy suggestions that would drive domestic investment and bring about sustainable economic growth in the long run.